Experience with Epifast® cryopreserved epidermal allograft in the treatment of superficial and deep second-degree burns: Retrospective study of 297 cases, 2010–2015. Issue 3 (July 2019) - Rodriguez-Ferreyra, Pablo; Gayosso-Cerón, Omar; Alonso-Campero, Rosalba; Tellez-Tellez, Adriana; Balderas-Sánchez, Ramiro; Funk, Martin; Reyes-Ibarra, Alma P.
Abstract: The objective of this study was to describe our experience with Epifast cryopreserved epidermal allograft (CEA) in children with second degree burns. We examined the number of days required for epithelialization, after the use of the Epifast® cryopreserved epidermal allograft (CEA). We examined medical records of 297 patients with superficial and deep second-degree burns treated with Epifast® CEA between January 2010 and December 2015 in the Pediatric Burn Unit of Nicolás San Juan Hospital, Toluca, Mexico. We included pediatric patients from newborn to 17 years of age, with burned body surface areas ≤30%, who were treated with tangential escharotomy and Epifast® CEA at the instructions of the treating physicians. Epithelialization occurred in an average of 7.5 days (SD = 7.4 days) after the initial application of Epifast® CEA. The most frequent epithelialization time was 5 days (24.2%), followed by 6–7 days (12.8%) and 4 days (10.8%). None of the 297 medical records contained a report of an adverse effect related to Epifast® CEA use.